Health‐related quality of life experiences in children and adolescents born with esophageal atresia: A Swedish–German focus group study. (16th September 2018) - Witt, Stefanie; Dellenmark‐Blom, Michaela; Flieder, Sofie; Dingemann, Jens; Abrahamsson, Kate; Jönsson, Linus; Gatzinsky, Vladimir; Chaplin, John Eric; Ure, Benno; Dingemann, Carmen; Bullinger, Monika; Sommer, Rachel; et al.
Abstract: Background: Esophageal atresia (EA) is a rare malformation of the esophagus, which needs surgical treatment. Survival rates have reached 95%, but esophageal and respiratory morbidity during childhood is frequent. Child and parent perspectives and cultural and age‐specific approaches are fundamental in understanding children's health‐related quality of life (HRQoL) and when developing a pediatric HRQoL questionnaire. We aimed to increase the conceptual and cross‐cultural understanding of condition‐specific HRQoL experiences among EA children from Sweden and Germany and investigate content validity for an EA‐specific HRQoL questionnaire. Methods: Eighteen standardized focus groups (FGs) with 51 families of EA children aged 2–17 years in Sweden ( n  = 30 families) and Germany ( n  = 21 families) were used to explore HRQoL experiences, which were content analyzed into HRQoL domains. The Swedish HRQoL domains were analyzed first and used as framework to evaluate HRQoL content reported in the German FGs. HRQoL experiences were then categorized as physical, social, and emotional HRQoL burden or resource. Results: One thousand nine hundred eight HRQoL statements were recorded. All nine EA‐specific HRQoL domains identified in the Swedish FGs (eating, social relationships, general life issues, communication, body issues, bothersome symptoms, confidence, impact of medical treatment, and additional difficulties due to concomitant anomalies) were recognized in the FGs held in Germany, and no additional EA‐specific HRQoL domain was found. The HRQoL dimensions referenced physical burden ( n  = 655, 34.5%), social burden ( n  = 497, 26.0%), social resources ( n  = 303, 15.9%), emotional burden ( n  = 210, 11.0%), physical resources ( n  = 158, 8.3%), and emotional resources ( n  = 85, 4.5%). Conclusion: This first international FG study to obtain the EA child and his or her parents' perspective on HRQoL suggests Swedish‐German qualitative comparability of the HRQoL domains and content validity for a cross‐cultural EA‐specific HRQoL questionnaire. EA children make positive and negative HRQoL experiences, but prominently related to physical and social burden, which underlines appropriate follow‐up care and future research.